The Albanian factor and the Varna crusade - Hauziński, Jerzy (Balcanica Posnaniensia. Acta et studia, 1997)
The article is devoted to the significance of the Albanian factor in the preparations for and course of the Varna Crusade of 1444. The author analyzes the problem of relations between the anti-Ottoman movement led by Skanderbeg and the Christian coalition fighting the Turks. This issue is of considerable importance for understanding the political and military conditions of the anti-Turkish struggles in the Balkans in the mid-fifteenth century. The aim of the study is to determine the extent of cooperation between the Albanian elites and the Christian camp, as well as to assess the influence of events in Albania on the course of the Varna expedition. The author draws on Venetian, Ragusan, and Ottoman sources, as well as chronicle accounts concerning Skanderbeg’s activities. The article demonstrates that the development of the Albanian resistance movement against the Ottomans coincided chronologically with the campaign of Władysław III and John Hunyadi. Skanderbeg, formally still in Ottoman service, simultaneously conducted secret negotiations with Venice, Ragusa, and Alfonso V of Naples. After the Christian victory at Niš in 1443, he seized Krujë and proclaimed an independent Albanian principality. Albanian actions forced the Turks to commit forces in Albania and partly hindered the concentration of Ottoman troops in Rumelia. The author emphasizes, however, that there is no convincing evidence of Skanderbeg’s direct participation in the Varna campaign or that Đurađ Branković actually prevented the Albanians from reaching Varna. The results of the analysis indicate that the Albanian factor played an important role in destabilizing the Ottoman position in the Balkans, although its significance for the Battle of Varna itself was limited.